The effect of intraoperative different oxygen concentrations on nausea and vomiting in morbidly obese patients undergoing laparoscopic bariatric surgery - Akel, Ramazan; Altun, Aysun Yildiz; Deniz, Ahmet; Aksu, Ahmet; Demirel, Ismail; Bestas, Azize; Bolat, Esef (Bayrakol Medical Publisher, 2023)
Aim: Postoperative nausea and vomiting (PONV) is a common problem due to many factors, and is especially seen in the first two hours after the operation. In this study, we aimed to investigate the effect of different intraoperative oxygen concentrations on nausea and vomiting in morbidly obese patients. Material and Methods: After the approval of the ethics committee, 206 patients who underwent laparoscopic bariatric surgery (LBS) in 2018 were included in the study by analyzing their files. The patients were divided into two groups according to the O2 concentrations used. Those given 30% oxygen (n=87) were determined as GrupLO, and those given 70% oxygen (n=119) were determined as GrupHO. Demographic data of the patients, body mass index, ASA score, hemodynamic parameters and anesthetic agents used, Apfel score, visual analog scale (VAS) score, PONV score, and the amount of metoclopramide administered in the post-anesthetic care unit (PACU) were recorded.Results: There was no significant difference between the groups in terms of demographic data and the anesthetic drugs used. PONV occurring in PACU was 66.66% (58/87) in Group LO and 44.53% (53/119) in Group HO. There was a statistically significant difference between the groups in the post-operative nausea-vomiting score (p<0.05). The amount of metoclopramide administered in PACU was lower in Group HO and it was statistically significant.Discussion: In this study, we found that the frequency of PONV was higher in morbidly obese patients who underwent LBS, and intraoperative high oxygen concentrations reduced the incidence of PONV.
54th National Turkish Anesthesiology and Reanimation Society -- 2020 -- ELECTR NETWORK
Keywords: Morbid Obesity; Intraoperative Oxygen Concentration; Postoperative Nausea-Vomiting; Laparoscopic Bariatric Surgery